PENERAPAN MODEL PEMBELAJARAN KOPERASI TIPE STAD TERHADAP KERJASAMA DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Pendidikan Agama Islam Siswa Kelas XII SMA Negeri 2 Lahat) - Zuhairin Zuhairin (DIADIK, 2020)
This research was conducted with the aim to find out 1) The application of the STAD cooperative learning model can increase student Cooperation, 2) The application of the STAD cooperative learning model can improve student learning achievement in Islam Religion Education subjects in Students and 3) The effectiveness of the application of type cooperative learning models STAD in improving student learning achievement in learning Islam Religion Education subjects   Class XII in SMA Negeri 2 Lahat. The problem in this study is that the learning methods used are less varied, the low attitude of student cooperation in participating in learning. This study used 25 subjects in PTK research, 20 in experimental class research, and 20 people in control class research.Data collection techniques in this study used observation and tests. The results of this study indicate that. The application of a STAD cooperative learning model can increase student cooperation in Islam Religion Education subjects. The application of a STAD cooperative learning model can improve student learning achievement in Islam Religion Education  subjects. The application of a STAD cooperative learning model can effectively improve student learning achievement in Islam Religion Education subjects class XII in SMA Negeri 2 Lahat.